Pendidikan Agama Kristen terhadap konsep diri anak usia 8-12 tahun - Yutersi, Noni; Mbo'oh, Ruth; Wagiyo, Wagiyo (Sekola Tinggi Teologi Sangkakala Jakarta, 2023)
ABSTRACTPositive self-concept has an important role in the formation of quality individuals, because self-concept plays a role in determining a person's behavior, according to the way he views himself. If he views himself as someone who does not have enough ability to carry out a task, then all his behavior will show his inability. Implementing Christian Religious Education for children who have a negative self-concept is not enough to provide learning materials for the Word to children. The material of God's word is of course very important, because the Bible characters that are given are usually figures who have a high positive self-concept. But the teacher factor is a very determining factor in instilling a positive self-attitude in children. Studying with friends who already have a positive self-concept is certainly very helpful in forming a child's self-concept. This research uses a quantitative approach with correlational methods. The population in this study were Sunday School children aged 8-12 years at Bethel Indonesia Church Karang Anyat, Central Jakarta. From the results of this research it can be concluded that there is a positive and significant influence between the large role of Christian religious education. And the influence is 71.3%. So the role of Christian religious education must be maintained so that children's positive self-concept becomes even better at Bethel Indonesia Karang Anyar Church, Sawah Besar, Central Jakarta. Keywords: Christian religious education, self-concept, children. ABSTRAKKonsep diri positif mempunyai peranan penting dalam pembentukan individu yang berkualitas, sebab konsep diri berperan dalam menentukan perilaku seseorang, sesuai dengan caranya memandang dirinya sendiri. Bila ia memandang dirinya sebagai orang yang tidak memiliki cukup kemampuan untuk melakukan suatu tugas, maka seluruh perilakunya akan menunjukkan ketidakmampuannya tersebut. Pelaksanaan Pendidikan Agama Kristen kepada anak yang memiliki konsep diri negatif tidak cukup memberikan materi pembelajaran firman kepada anak-anak. Materi firman Tuhan tentu saja sangat penting, karena tokoh-tokoh Alkitab sebagai yang diberikan biasanya adalah tokoh-tokoh yang memiliki konsep diri positif yang tinggi. Tetapi faktor guru adalah faktor yang sangat menentukan dalam menanamkan sikap diri positif kepada anak. Belajar bersama teman-temannya yang sudah memiliki konsep diri positif tentu sangat membantu pembentukan konsep diri anak. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Populasi dalam penelitian ini adalah anak-anak Sekolah Minggu usia 8-12 tahun di Gereja Bethel Indonesia Karang Anyat, Jakarta Pusat. Dari hasil penelitian ini dapat disimpulkan bahwa terdapat pengaruh yang positif dan signifikan antara Peranan Pendidikan Agama Kristen yang bersifat besar. Dan pengaruhnya sebesar 71,3%. Jadi Peranan Pendidikan Agama Kristen harus dipertahankan agar Konsep Diri Positif anak semakin baik lagi di Gereja Bethel Indonesia Karang Anyar, Sawah Besar, Jakarta Pusat.Kata kunci: Pendidikan Agama Kristen, Konsep Diri, Anak.